Trehalose enhances osmotic tolerance and suppresses lysophosphatidylcholine‐induced acrosome reaction in ram spermatozoon. (1st October 2014) - Ahmad, E.; Naseer, Z.; Aksoy, M.; Küçük, N.; Uçan, U.; Serin, İ.; Ceylan, A.
Summary This study was aimed to investigate the influence of trehalose on osmotic tolerance and the ability of ram spermatozoon to undergo acrosome reaction induced by lysophosphatidylcholine (LPC). In experiment 1, the diluted ejaculates were exposed to anisosmotic fructose solutions (70, 500, 750 and 1000 mOsm l−1) with or without 50 mm trehalose. The presence of trehalose in hyperosmotic conditions enhanced (P < 0.05) the percentage of live, live‐intact and intact spermatozoa. Similarly, trehalose enhanced (P < 0.05) the live and live‐intact spermatozoa during hypo‐osmotic conditions. In experiment 2, the centrifuged ejaculates were diluted with TCG only or TCG containing either 50 or 100 mm trehalose. The acrosome reaction was induced by LPC. The percentage of acrosome‐reacted spermatozoon was less (P < 0.05) in trehalose‐supplemented groups compared to control. In experiment 3, the ejaculates were cryopreserved in an extender containing 0 mm (control), 50 mm or 100 mm trehalose. Supplementation of extender with trehalose, either 50 mm or 100 mm, enhanced the cryosurvival rate (P < 0.05) compared to the control. In conclusion, the presence of trehalose in anisosmotic conditions enhances the osmotic tolerance, cryosurvival rate of ram spermatozoon and suppresses their ability to undergo LPC and cryo‐induced acrosome reaction.